Trainini cardiac fulcrum in the fetal heart - Sosa Olavarría, Alberto (2023)
Objective: To demonstrate by dissection of anatomical specimens and prenatalultrasonographic images of the fetal heart the presence of the cardiac fulcrum asa fixation structure supporting the helical myocardial band. Methods: Six heartsof fetuses between 20-24 weeks of gestational age resulting from spontaneousabortions were dissected, finding the cardiac fulcrum in the proximity of the aortaand connections with myocardial fibers. In 50 singleton pregnancies with fetusesbetween 18-37 weeks of gestation, fetal cardiac ultrasonography was used to obtain2D, Doppler, color and three-dimensional modalities, STIC, HD Flow and speckletracking, images, fulcrum measurements and its kinetics. Results: With the describedstrategy, the presence of the cardiac fulcrum or myocardial lever was identifiedand demonstrated, establishing its anatomical characteristics, connections withmyocardial fibers of the cardiac loop and the biometry according to gestationalage. A hypothesis on the biomechanics or kinetics of the fulcrum during the cardiaccycle is formulated. Conclusions: In order for the heart to fulfill its function as anaspirating and impelling pump, it must have a support point, a lever or fulcrum, whichconstitutes a sort of muscle-tendon unit. This lever presents mixed displacementsduring myocardial torsion and detorsion. Its diameters increase progressively asgestation advances.